Memanfaatkan E-Commerce Dalam Meningkatkan Pemasaran Kopi Desa Belitar Seberang kecamatan Sindang Kelingi Kabupaten Rejang Lebong Provinsi Bengkulu - Yudi Irawan Abi; Yesi Indian Ariska; Nia Indriasari; Iswidana Utama Putra; Hasan Abdulah (Jurnal Dehasen Untuk Negeri, 2023)
The development of technology, communication devices that make everyone who has a smartphone connected to the internet makes it easier for prospective buyers to find the desired item through their communication device. a very promising opportunity to be developed. The implementation of this community service aims to apply e-commerce to the sale of these coffee products. In the application of e-commerce to coffee products, it is necessary to provide insight to business actors to maintain product quality because it relates to buyer trust, providing complete and fast information, openness to information from customers and the existence of coupons and discounts for regular customers Transparency of product delivery information, trace the existence of the goods sent and good cooperation between the seller and the buyer must be maintained properly. Vigilance against online fraud is also information that needs to be given to business actors in the implementation of this community service. So that at the end of the implementation of this community service, understands online business opportunities, can compete healthily, gain the trust of its customers. the creation of social media accounts and e-commerce interfaces. The product marketing process went quite well as indicated by the addition of the number of visitors on social media accounts after 2 months. Marketing continues to be carried out by utilizing other social media.